Tunable magnetic properties of nanoparticle two-dimensional assemblies addressed by mixed self-assembled monolayers - Pichon, Benoit P (Langmuir : the ACS journal of surfaces and colloids, 2011)
Assemblies of magnetic nanoparticles (NPs) are intensively studied due to their high potential applications in spintronic, magnetic and magneto-electronic. The fine control over NP density, interdistance, and spatial arrangement onto substrates is of key importance to govern the magnetic properties through dipolar interactions. In this study, magnetic iron oxide NPs have been assembled on surfaces patterned with self-assembled monolayers (SAMs) of mixed organic molecules. The modification of the molar ratio between coadsorbed 11-mercaptoundecanoic acid (MUA) and mercaptododecane (MDD) on gold substrates is shown to control the size of NPs domains and thus to modulate the characteristic magnetic properties of the assemblies. Moreover, NPs can be used to indirectly probe the structure of SAMs in domains at the nanometer scale